PRIORITAS PEMELIHARAAN IRIGASI SUB DAS KALI BRANTAS KOTA BATU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Cholilu Rohman; Umboro Lasminto; Theresia Sri Sidharti (Journal of Civil Engineering, 2018)
This paper presents the results of the study of one of the alternative decision support systems in determining the priority of irrigation maintenance. One of the obstacles in maintaining irrigation assets is the limited budget, hence the need for priority maintenance of irrigation. Batu City as an agricultural area, has not applied objective assessment criteria in determining the priority scale of irrigation asset maintenance to support the success of agriculture. Especially the irrigation area of Kali Brantas Sub Watershed which is the downstream area of Batu City, there are still many damaged irrigation assets infrastructure. This study aims to determine the priority of irrigation maintenance of Kali Brantas Sub Watershed Batu City. Analysis using Simple Additive Weighting method with the following stages: The assessment of each criterion directly in the field (Physical Condition, Functioning, Service Area and maintenance cost) according to Regulation of Minister of Public Works No. 13 / PRT / M / 2012, , determine the rating of each alternative match, normalization of alternative value of each criterion and ranking of normalization product with weight of importance. The result of the analysis shows that irrigation infrastructure which become the first priority in irrigation maintenance activity of Kali Brantas Sub Watershed Batu City is Genengan Dam. For second priority up to five consecutive are; Bend Beji I, Beji II, Ngukir Mranak II and Ngukir Mranak I Dam..